The resilience of tourism at Georgetown heritage sites: insights from local community engagement during COVID-19 pandemic / Ahmad Nazrin Aris Anuar ... [et al.] - Aris Anuar, Ahmad Nazrin; Rahmat, Nor Izzatie; Ahmad, Che Bon; Nasir, Rabiatul Adawiyah; Zainuddin, Ainur Zaireen (UiTM Press, 2024)
The Coronavirus Disease 2019 (COVID-19) virus rapidly spread worldwide, evolving into a significant pandemic that has impacted nearly every country. Georgetown, as a heritage site, has witnessed distinct effects of the crisis on cultural heritage sites and stakeholders, along with various economic implications. The primary impact on this heritage site has been a decline in visitor numbers due to government imposed preventive measures such as movement restrictions. These measures have significantly affected the tourism sector's economy. However, local community engagement was insufficient during the strategic planning for tourism development at heritage sites. This research aims to understand the involvement of the local community in heritage sites at Georgetown during COVID-19. Specifically, the objective is to identify the challenges faced by the local community and tourism at heritage sites during COVID-19. This study utilised a quantitative approach by collecting data through an online survey questionnaire. Data analysis was conducted using SPSS (Statistical Package for the Social Sciences), which revealed the challenges and opportunities posed by the pandemic at heritage sites. The findings underscored the importance of strong collaboration between the local community and authorities during the COVID-19 pandemic. Additionally, promoting domestic tourism among residents can help sustain cultural heritage and sensitivity. Organisations and management should prioritise strategies for engaging with the local community to sustain tourism at heritage sites while preserving and conserving their historical value.